Myanmar Monthly Food Price Report – November 2024 - Myanmar Agrifood Program for Strategy and Analysis (International Food Policy Research Institute, 2024)
The rapidly evolving food security situation in Myanmar requires a high frequency, systematic and comprehensive approach to monitoring. The Myanmar monthly food price report synthesizes food price trends using publicly available datasets, focusing on key agricultural crops and highlighting regional differences in rice prices. By analyzing these trends, the report aims to provide insights into the broader agricultural market and the factors driving food price fluctuations in Myanmar.